PENGENDALIAN HAMA PENGGEREK TONGKOL JAGUNG Helicoverpa armigera HUBNER. (LEPIDOPTERA : NOCTUIDAE) DENGAN Beauveria bassiana strain lokal PADA PERTANAMAN JAGUNG MANIS DI KABUPATEN DONGGALA - Nurkhasanah Nurkhasanah (Universitas Tadulako, 2008)
The attack of pod borer Helicoperva armigera Huebner (Lepidoptera:Noctuidae) on corn ear stems represent the main constraint of sweet corn planting development in Donggala Regency Central Sulawesi. The biological control using a pathogen insect (entomopathogen) as one of the integrated pest control components can be developed to overcome this problem. One type of the pathogenic insect is a Beuverria bassiana fungi.The research aims were to identify the effectiveness of various concentrations and application time interval of B. bassiana as bioinsecticide to control of H. armigera pod borer. The experiment used a Randomized Block design with two factors consisting of B. bassiana concentrations (K): k 1 = 0,4, k 2 = 0,6 and k 3 = 0,8, and time interval of B. bassiana applications (W) : w 1 = 5 d, w 2 = 7 d, and w 3 = 9 d. Each treatment was replicated 3 times; therefore, there were 27 experimental units in total. The parameters observed were: (i) density of larva population (ii) mortality of larva, and (iii) percent of ear corn stem damage. Data were analysed using the analysis of variance, and differences between means was tested using honest significant difference (HSD) test at 5%. The research results showed that the concentration and the application time interval of B. bassiana each had significant effect on all parameters observed but their interaction effect was insignificant. The treatment k 2 w 3 (0.6 mg B. bassiana/L water applied every 9 d) was more effective in suppressing the population density, the larva mortality and the ear corn stem damage percent than other treatments. Considering the negative impacts of using chemical insecticide, B. bassiana bioinsecticide can be used as an alternative control of sweet corn pod borer H. armigera.